Cowboy to the core - Yates, Maisey (Yates, Maisey. Gold Valley novel., 2019)
When horse trainer Jamie Dodge comes to work for him on his family's ranch, champion saddle bronc rider Gabe Dalton hopes that she is the one woman who can soothe his restless soul but fears the consequences if he is mistaken.